P135 Treatment of lung disease in alpha-1 antitrypsin deficiency: a systematic review. (15th November 2016) - Edgar, RG; Patel, M; Bayliss, S; Sapey, E; Turner, AM
Abstract : Introduction: Alpha-1 Antitrypsin Deficiency (AATD) is a rare genetic condition predisposing individuals to COPD. The majority of treatment for AATD is similar to non-AATD related COPD; intravenous augmentation of Alpha-1 Antitrypsin is a specific treatment but is inequitably used across Europe and not used in the UK. There is a pressing need to systematically investigate efficacy since the publication of a new placebo controlled RCT and to identify patient centred, clinically meaningful outcomes. 1 Methods: A systematic review was conducted using standard review methodology with meta-analysis and narrative synthesis (registered with PROSPERO-CRD42015019354). Eligible studies were those of any treatment used in severe AATD. RCT's were the primary focus however case series and uncontrolled studies (n > 10 patients receiving treatment or usual care, with baseline and follow-up data >3 months), were eligible for inclusion to ensure natural history of disease outside RCT's could be determined. Results: 7296 unique records were reviewed with 51 trials analysed on 5632 participants: 26 AAT-augmentation (3 for meta-analysis); 17 surgical intervention (5 Lung volume reduction (LVR) surgery, 1 Bronchoscopic valve LVR and 11 Lung transplantation); 3 medical interventions and 3 trials completed but not published. Meta-analysis of AAT-Augmentation demonstrated slower lung CT density decline, difference 0.79 g/l/year (95% CI: 0.29–1.29; p = 0.002), and a small increase in annual exacerbations 0.29/year (95% CI: 0.04–0.54; p = 0.02) compared to placebo (Figure 1 ). Survival benefit of transplant was observed in one study (p = 0.006) but not in a second with more stringent matching for groups; however significant improvements in health status, total SGRQ and all domain scores, at one year (p < 0.01) were observed. Mortality post lung transplant was comparable between AATD and non-AATD related COPD cohorts. Surgical lung volume reduction demonstrated inferior outcomes when compared to non-AATD related emphysema. Conclusion: CT density, FEV1, DLCO, health status and exacerbation rates were frequently used as outcomes in AATD related treatment trials. AAT-Augmentation is able to slow the progression of severity of emphysema when measured by CT density change compared to placebo. This systematic review will help assist in the improved monitoring and management of patients with AATD. Reference: 1 Chapman KR, et al . Intravenous augmentation treatment and lung density in severe α1 antitrypsin deficiency (RAPID): a randomised, double-blind, placebo-controlled trial. The Lancet 2015;386 (9991):360–368.